Analysis of the coefficient of variation in shear and tensile bond strength tests Análise do coeficiente de variação em testes de resistência da união ao cisalhamento e tração - Fábio Lourenço Romano; Gláucia Maria Bovi Ambrosano; Maria Beatriz Borges de Araújo Magnani; Darcy Flávio Nouer (University of São Paulo, 2005)
The coefficient of variation is a dispersion measurement that does not depend on the unit scales, thus allowing the comparison of experimental results involving different variables. Its calculation is crucial for the adhesive experiments performed in laboratories because both precision and reliability can be verified. The aim of this study was to evaluate and to suggest a classification of the coefficient variation (CV) for in vitro experiments on shear and tensile strengths. The experiments were performed in laboratory by fifty international and national studies on adhesion materials. Statistical data allowing the estimation of the coefficient of variation was gathered from each scientific article since none of them had such a measurement previously calculated. Excel worksheet was used for organizing the data while the sample normality was tested by using Shapiro Wilk tests (alpha = 0.05) and the Statistical Analysis System software (SAS). A mean value of 6.11 (SD = 1.83) for the coefficient of variation was found by the data analysis and the data had a normal distribution (p>0.05). A range classification was proposed for the coefficient of variation from such data, that is, it should be considered low for a value lesser than 2.44; intermediate for a value between 2.44 and 7.94, high for a value between 7.94 and 9.78, and finally, very high for a value greater than 9.78. Such classification can be used as a guide for experiments on adhesion materials, thus making the planning easier as well as revealing precision and validity concerning the data. O Coeficiente de variação é uma medida de dispersão que independe da escala de unidades, permitindo comparação de resultados experimentais de variáveis diferentes. Seu cálculo é imprescindível em experimentos laboratoriais de adesão, pois a partir dele é possível verificar a precisão e confiabilidade do experimento. O objetivo deste trabalho foi avaliar e sugerir uma classificação do coeficiente de variação (CV) em experimentos in vitro que envolveram testes de resistência ao cisalhamento e / ou tração. Foram analisados 50 trabalhos de periódicos nacionais e internacionais, sendo que todos avaliaram a adesão em ensaios laboratoriais. Foram coletados em cada artigo dados estatísticos que permitiram estimar o coeficiente de variação, pois nenhum deles apresentava esta medida calculada. Os dados coletados foram organizados em Planilha Excel, sendo a normalidade da amostra testada pelo teste de Shapiro Wilk (alfa=0,05) utilizando o programa Statistical Analysis System (SAS). Pela análise dos dados, tendo os mesmos apresentados distribuição normal (p>0,05) foi encontrado um CV médio de 6,11 com desvio-padrão de 1,83. A partir destes dados foram propostas faixas de classificação para o coeficiente de variação, ou seja, este coeficiente deve ser considerado baixo até um valor de 2,44; médio entre 2,44 - 7,94, alto entre 7,94 - 9.78 e muito alto acima de 9,78. Esta classificação poderá ser usada como guia para experimentos de adesão, facilitando o planejamento, revelando a precisão e validade dos dados.